14.45 Relationships between walking speed, cognition & brain pathologies: an imaging study of the 1946 birth cohort. Issue 12 (14th November 2019) - Buchanan, Sarah M; Parker, Thomas D; Lane, Christopher A; Keshavan, Ashvini; Keuss, Sarah E; Schrag, Anette E; Fox, Nick C; Richards, Marcus; Schott, Jonathan M
Abstract : Introduction: Slowing of gait is associated with risk of cognitive decline, but whether this is due to brain pathology or a consequence of normal neural ageing remains unclear. We investigate associations between gait speed, cognitive test scores, white matter hyperintensity (WMH) volume, whole brain volume (WBV) and β-amyloid load in a sample of healthy older adults born in the same week of March 1946 in mainland Britain. Methods: 502 participants underwent quantitative gait measurement, neuropsychological assessment, structural MRI and 18F-florbetapir amyloid PET. Excluding individuals with major neurological disease or missing data, 374 individuals (age 70.6 ±0.69 years) were analysed. Results: Mean self-paced walking speed was 1.44 ± 0.19 ms-1. Slower walking speed was associated with lower performance on the Digit-Symbol Substitution test (p=0.007) and MMSE (p<0.05), but not tests of memory or fluid intelligence. These associations were not significantly altered by adjusting for WBV, WMH volume or PET evidence of cerebral β-amyloid deposition. Conclusion: In healthy older adults, gait speed is associated with processing speed and global cognition, but not with tests of non-verbal reasoning or memory. These associations were not accounted for by the measured cerebral pathologies. Further analyses incorporating region-specific and microstructural brain imaging are required.